On differential temperature controller setpoint selection for active photovoltaic-thermal (PV-T) systems - Magalhães, Pedro (2021)
Active photovoltaic-thermal (PV-T) systems for solar heating and electricity generation are likely to employ the same differential temperature pump controllers as equivalent non-hybrid solar thermal (ST) systems. However, the typical controller setpoint selection methods for cost-effective and stable pump operation fail to consider the effect on photovoltaic (PV) electricity generation taking place in PV-T systems. Analytical relations for the same goals were derived to anticipate this influence using the steady-state Florschuetz PV- T collector model and compared with equivalent numerical methods relying on an extension of the Perers model designed to encompass PV-T collectors, namely by modelling electricity generation and the associated thermal performance reduction. Both methods indicate the minimum turn-on and turn-off setpoints for cost-effective and stable operation increase and decrease, respectively, relative to those for non-hybrid operation of PV-T systems or equivalent non-hybrid systems, and more so at higher irradiance levels, though the variations are shown not to be significant for a range of PV-T systems represented and can be reasoned to be inflated or of limited practical relevance. In conclusion, the effect of pump operation on electricity generation is not predicted to be a determining factor for differential temperature controller setpoint selection in PV-T systems.